Participation in River Basin Planning Under the Water Framework Directive – Has it Benefitted Good Water Status? - Marlene Rimmert; Lucie Baudoin; Benedetta Cotta; Elisa Kochskämper; Jens Newig (Water Alternatives, 2020)
The participation of societal groups and of the broader public has been a key feature in implementing the European Water Framework Directive (WFD). Non -state actor participation in the drafting of river b asin management plans was expected to help achieve the directive's environmental goals, but the recent literature leaves us doubtful whether this has in fact been the case. This study examines a structured online survey of 118 public water managers, covering the six biggest European Union states ofFrance, Germany, Italy, Poland, Spain and the UK. We assess multiple facets of participation, for example the involved actors, the intensity of communication exchange, and participants' influence on planning. Results show that participatory WFD implementation has included a wide range of actor groups but rarely citizens, and that there has been minimal provision for interactive communication. The value of active involvement to the reaching of environmental goals was assessed as limited and that of public consultation as insignificant. Participants who were actively involved mainly contributed by advocating for stronger environmental standards and by providing implementation-relevant knowledge. Potential reasons for the overall poor record of participation include the strong influence of agriculture and the lack of public interest. Our findings suggest that, in hindsight, the European Commission's conviction that participation benefits good water status appears overly naïve.
Keywords: 710; Active involvement; river basin management; ecological outcomes; mandated participatory planning; European water governance; participatory governance; stakeholder involvement